Successive Matrix Squaring Algorithm for Computing the Generalized Inverse AT,S(2) - Xiaoji Liu; Yonghui Qin (Journal of Applied Mathematics)
We investigate successive matrix squaring (SMS) algorithms for computing the generalized inverse AT,S(2) of a given matrix A∈Cm×n.